2020
DOI: 10.1002/aoc.5603
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and penta‐nuclear self‐assembled silver(I) complexes of pyrazolyl s‐triazine ligand; synthesis, structure and antimicrobial studies

Abstract: The self‐assembled [Ag (PTDM)NO3] (1), [Ag (PTDM)2(H2O)]ClO4.H2O (2) and [Ag5(PTDM)4(H2O)6(ClO4)4]ClO4.2H2O (3) complexes were synthesized by the direct mixing of AgX (X = NO3¯ or ClO4¯) and 4,4′‐[6‐(3,5‐dimethyl‐1H‐pyrazol‐1‐yl)‐1,3,5‐triazine‐2,4‐diyl]dimorpholine (PTDM) ligand in water–methanol mixture. The coordination numbers of silver range from three to five. Complex 3 is a rare case in which one nitrogen atom from the same s‐triazine core of the PTDM ligand has a μ(1,1) bridging mode between Ag1 and Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…[30,31] The ligand field parameters Dq = 832.5 cm −1 , B = 823 cm −1 , β 35 = 0.847 cm −1 , ν 2= ν 1 = 2.007, and σ = 18.06% for the cobalt complex supported its octahedral configuration. [32,33] The nickel complex revealed four bands at 10235, 17520, 24850 and 32750 cm −1 consistent with 3…”
Section: Electronic Spectra and Magnetic Measurementsmentioning
confidence: 71%
See 1 more Smart Citation
“…[30,31] The ligand field parameters Dq = 832.5 cm −1 , B = 823 cm −1 , β 35 = 0.847 cm −1 , ν 2= ν 1 = 2.007, and σ = 18.06% for the cobalt complex supported its octahedral configuration. [32,33] The nickel complex revealed four bands at 10235, 17520, 24850 and 32750 cm −1 consistent with 3…”
Section: Electronic Spectra and Magnetic Measurementsmentioning
confidence: 71%
“…Therefore, to overcome the growing resistance of antimicrobial agents, researchers are developing new classes of antimicrobial drugs with adequate mechanisms. In recent years, transition metal complexes, [1][2][3][4][5] which have attracted substantial interest in bioinorganic chemistry as metal-based drugs, have been found to be good candidates for their efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Silver(I) complexes of pyrazolyl s-triazine were observed to have antimicrobial properties which depended on the nuclearity of the complexes. [8] An investigation by El-Ansary et al [9] showed the enhanced antimicrobial activity of Agcoumarin complexes compared with the free ligands, and similar results were also obtained for Ag-isonicotinic acid complexes. [10] Interestingly, Ag-naphthalenol Schiff base complexes showed manifold pharmaceutical therapy, namely, anticancer, antioxidant and antimicrobial offering combination drug treatment at one goal.…”
Section: Introductionmentioning
confidence: 78%
“…Additionally, some Pd(II)-s-triazine complexes have been constructed and assessed against breast cancer cell lines (MCF7 and MDA-MB-231) and have exhibited good potentials [15,16]. The design of new s-triazinebased ligands and their coordination modes with different metal centers is still a challenge [17][18][19]. Recently, Barakat et During our study, we have explored the utility of the hydrazono-s-triazine-based ligand towards metalation with the divalent platinum ion to synthesize a new Pt(II) complex based on s-triazine hydrazone ligand (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some Pd(II)- s -triazine complexes have been constructed and assessed against breast cancer cell lines (MCF7 and MDA-MB-231) and have exhibited good potentials [ 15 , 16 ]. The design of new s -triazine-based ligands and their coordination modes with different metal centers is still a challenge [ 17 , 18 , 19 ]. Recently, Barakat et al designed, synthesized and characterized a new hydrazono- s -triazine-based ligand and later explored the coordination chemistry of this ligand with a palladium(II) center.…”
Section: Introductionmentioning
confidence: 99%